W ciemnościach tunelu, czyli o zjawisku leksykalnego plateau - Seretny, Anna (Postscriptum Polonistyczne, 2020)
Level B (Independent user) is a specific stage in the process of language education because it consists of two completely different levels of language proficiency. The objectives and content of teaching on B1 level (Threshold or intermediate) and B2 (Vantage or upper intermediate) are incompatible when it comes to quantity and quality. It is necessary to choose different methods of teaching/learning at B2 level, otherwise the progress in learning can be slowed (the language learning plateau). The aim of the article is to present the specifics of learning vocabulary at B2 (Vantage or upper intermediate) level and provide some didactic strategies that can help teachers to minimize the plateauing of language learning and its effects. They can also help students in learning new vocabulary effectively.